Accessibility measurement of highway transportation networks based on closeness-accessibility - Yuanyuan Zhang; Weidong Song; Jinguang Sun; Peng Dai (PLoS ONE, 2025)
Accessibility is a central concept in transport geography research. Quantitative assessment of highway network accessibility aids in assessing road network efficiency, urban layout optimization, functional zoning and sustainable development. Current metrics for assessing accessibility primarily concentrate on examining the relationship between land use and transportation networks, overlooking the influence of trip demand and node centrality on highway network accessibility. To clarify these impacts, borrowing from concepts in network science, we propose a new centrality measure called closeness-accessibility. This approach utilizes closeness centrality of network nodes as a weight to assess the interaction potential between nodes, enhances the gravity-based accessibility of demand points based on trip time, and incorporates network connectivity to evaluate the impact of travel demand on highway network accessibility and the significance of node centrality non-uniformity. Liaoning Province provides an empirical case study to showcase the usefulness of closeness-accessibility. The findings indicate a positive correlation between the gravity-based and closeness-accessibility generated by various β values, showing a linear relationship between the two. Closeness-accessibility takes into account the number and centrality of demand points in influencing travel demand, enhances the calculation of the shortest paths of the spatial location of the demand nodes, and improves the accuracy of accessibility calculations. Nodes with higher centrality exhibit greater accessibility, leading to clearer delineation of accessibility levels for demand points and highway network across different regions. In Liaoning Province, the areas with high demand attraction and highway network accessibility are concentrated in the coastal area and the provincial capital center, while accessibility services in western part are inadequate. Although all grades of highway accessibility service are high, higher-grade highways sometimes show lower accessibility. This research offers a methodological tool for transportation experts and holds significant importance in the scientific and effective evaluation of transportation system performance.